Characterization of composite active edible film functionalized through reinforced Pimpinella anisum essential oil. Issue 8 (7th June 2022) - Bharti, Sanjay Kumar; Pathak, Vikas; Arya, Anita; Alam, Tanweer; Singh, Vinod Kumar; Verma, Arun Kumar; Rajkumar, Vincentraju
Abstract: This work aimed to develop biobased composite active edible film of tapioca starch‐κ‐carrageenan reinforced with Pimpinella anisum essential oil and to evaluate the effect of reinforcement on physico‐mechanical, barrier, optical, and antimicrobial properties. Nineteen different components of oil were identified with distinct chromatogram peaks using Gas Chromatography–Mass Spectroscopy. The Minimum Inhibitory Concentration value of essential oil against standard test bacteria ranged between 0.6% and 1%. The dynamic oscillatory rheological measurements of film‐forming solution revealed solid‐like viscoelastic behavior. Incorporation of oil in the film caused significant ( p  < 0.05) increase in moisture absorption, b value, total color difference (∆E) haziness, transparency, and significant ( p  < 0.05) decrease in elongation at break, moisture, whiteness index, and L* value. Antimicrobial functionality by disc diffusion of treated films was found highly significant ( p  < 0.01). The results of the study provide a promising potential of composite active edible film with enhanced antimicrobial functionality. Novelty impact statement: The new‐fangled bio composite blend is functionalized with Pimpinella anisum essential oil. The study originally demonstrates the effect of incorporation of P. anisum essential oil on the quality and acceptability of unique bio‐composite edible film. The formed composite active edible film can be commercially exploited to provide better quality and safety to various foods with eco‐friendly disposal.